Media Video Sebagai Metode Katekese Untuk Berkatekese Bagi Remaja di Era Digital - Amsikan, Modesta (JURNAL PROPHETA, 2021)
This writing aims to describe the catechesis method using video as a catechesis method for adolescents in the digital era. This main objective is described in threeobjectives, namely, first, to describe the reality of the digital era as the context oftoday's youth. Second, describe the catechesis methods for youth so far and show theirshortcomings in responding to the digital era. Third, describe the catechesis methodusing video media and show its superiority in catechesis for teenagers in the digital era.This writing is a result of qualitative research with document study researchmethods. The data studied are secondary data in the form of literature related to the variables. Data collection is done by means of documentation or archive techniqueswhere the author searches for and reads various relevant literatures on the studyvariables and conducts studies and quotes various relevant theories and studies toexplore various information and related factual data. Then the data analysis technique iscarried out with a flow model starting from data collection, data reduction, data displayand conclusions. Based on the results of research and discussion, it can be concluded that he realityof the digital era has influenced today's youth and caused certain characters such asdigitally oriented, practical and instant, confident, loving diversity, having a passion forsharing, hyper customization, driven to success. The catechesis methods that are usuallycarried out with teenagers have so far paid less attention to the digital character withinthem. These methods do not start the catechesis with a description of a concretesituation or if it is made then the description of the situation is not conveyed in aninteresting and touching way. This is not in accordance with the character of today'steenagers who are digitally oriented, like practical and up-to-date things. Catechesiswith video media is a catechetical method that pays attention to the digitalcharacteristics of adolescents. This method uses video as material for catechesis,describing concrete situations, studying the Scriptures, and stimulating the expression ofreal intentions or actions.